Properties of glass fiber reinforced self compacting concrete - Wong, Choon Siang (2012)
Self Compacting Concrete (SCC) is able to flow under its own weight and completely fill the formwork, even in the presence of congested reinforcement, without any compaction, while maintaining homogeneity of the concrete. Majority of concrete cast rely on compaction to produce good quality concrete. However, compaction is difficult to be done in conditions where there are dense reinforcement and large casting area. Usage of SCC will overcome the difficult casting conditions and reduce manpower required. Addition of fibers will enhance the tensile and ductile behaviour of concrete with brittle nature. SCC was added with relatively short, discrete, and discontinuous glass fibers to produce Glass Fiber Reinforced Self Compacting Concrete (GFRSCC). The purpose of this study is to investigate the workability and mechanical properties of plain SCC and GFRSCC. Control concrete (NC), plain SCC, and GFRSCC samples were prepared. Water-cement ratio of 0.40 was used for all concrete mixes. The fiber and brand of superplasticizer used were alkaline-resistance glass fiber and Rheobuild 1100, respectively. Three fiber contents of 0.5%, 1.0%, and 1.5% by volume of concrete were utilised in this study. The laboratory testing included slump flow test, L-Box test, sieve segregation resistance test, density test, ultrasonic pulse velocity (UPV) test, compressive strength test, splitting tensile strength test, and flexural strength test. The dosage of superplasticizer required increased as fiber content increased. Plain SCC and GFRSCC were highly workable than NC. The experimental results show that plain SCC exhibited higher compressive strength than NC and GFRSCC. The splitting tensile strength of NC was higher than plain SCC and GFRSCC due to negative effect of superplasticizer added. The flexural strength of NC was slightly higher than plain SCC. All GFRSCC exhibited higher flexural strength than plain SCC. The optimum fiber content was 1.0% by volume of concrete. GFRSCC with 1.0% fiber content developed higher load at first crack and ultimate load than NC and plain SCC slabs.